Twenty years of Journal of Rubber Research (1996-2015): A bibliometric study / Nor Faezah Ismail - Nor Faezah , Ismail (2018)
The position of the Malaysian Rubber Board (MRB) in rubber research and development is to develop, transfer, commercialise and promote research findings. The role of Journal of Rubber Research (JRR) published by the MRB in diffusion of data concerning researches in the field of rubber research and development activities is of premier importance. JRR is one of the oldest and leading rubber research journal in the country since 1929. Because of the JRR’s maturity, productivity and its quality, therefore, this study presents a bibliometric study of the JRR from 1996 to 2015. The study covers the volume of articles, patterning of authorship, the extent of acknowledgement as included in research articles, types and frequency of occurrence. The results indicate that there is a consistent balance in the journal’s publication productivity, with an average number of 21 articles produced per year, an average acknowledgment of 2.0 per item and the most common type of acknowledgements relate to the technical support. In terms of authorship pattern, results indicate multi-authoring and increased collaboration among rubber researchers. This study analyses the performance of scientists and productivity of researchers for the year 2007 until 2015 using the scientific output gathered by Web of Science (WoS). Data from WoS involves keeping track of the citation works and highlighting the impact and influence of the research journal. Citation to JRR articles were obtained from WoS which revealed that out of the 178 articles published between 2007 and 2015, 43.8% (78) have been cited from time to time. This implies that JRR articles are appealing to both local and international researchers as the study showed that these articles formed the source of knowledge in scholarly journals (158 times) and books or book chapters (11 times). JRR articles which are cited by top journals are Journal of Applied Polymer Science (12), Rubber Chemistry and Technology (11), KGK-Kautschuk Gummi Kunststoffe (6) and BMC Plant Biology (4).